Further analyses of the structural organization of Homo luzonensis teeth: Evolutionary implications. Issue 163 (February 2022) - Zanolli, Clément; Kaifu, Yousuke; Pan, Lei; Xing, Song; Mijares, Armand S.; Kullmer, Ottmar; Schrenk, Friedemann; Corny, Julien; Dizon, Eusebio; Robles, Emil; Détroit, Florent
Abstract: The species Homo luzonensis has recently been described based on a set of dental and postcranial elements found at Callao Cave (Northern Luzon, Philippines) and dated to at least 50–67 ka. Seven postcanine maxillary teeth are attributed to this taxon, five of them belonging to the same individual (CCH6) and representing the holotype of H. luzonensis, whereas the isolated upper premolar CCH8 and the upper third molar CCH9 are paratypes of the species. The teeth are characterized by their small dimensions associated with primitive features, as also found in Homo floresiensis, another hominin having evolved in an insular environment of Southeast Asia. Postcranial bones of the hands and feet of H. luzonensis and H. floresiensis show Homo habilis –like or australopith-like features, whereas cranial and dental morphology are more consistent with the Asian Homo erectus morphology. Due to this mosaic morphology, the origin and phylogenetic relationships of both H. luzonensis and H. floresiensis are still debated. To test the hypotheses that H. luzonensis derives from H. erectus or from an earlier small-brained hominin, we analyzed the µCT scans of the teeth. We investigated both external and internal tooth structure using morphometric methods including: crown outline shape, tooth crown tissue proportions, enamel-dentine junction shape, and pulp morphology. Homo luzonensis external crown morphology aligns more with H. erectus than with H. habilis/H. rudolfensis . The internal structural organization of H. luzonensis teeth exhibits more affinities with that of H. erectus and H. floresiensis than with Neanderthals and modern humans. Our results suggest that both H. floresiensis and H. luzonensis likely evolved from some H. erectus groups that dispersed in the various islands of this region and became isolated until endemic speciation events occurred at least twice during the Pleistocene in insular environments.